The little things [large type] - Pike, M. Jean (Thorndike Press Large Print Christian Romance, 2024)
"A decade ago, Rochelle Delany made a decision that changed her life forever. Wanting more than just football games and potluck suppers, she boarded a bus for California and didn't look back. But instead of a glamorous life, she became trapped in a nightmare of labor trafficking. Now, she's made a daring escape and returns home to Ohio. Sandy Fairbrother has a problem with trust. Twice betrayed, he now puts his faith only in God. He's a single dad doing his best to grow his construction business and raise his young son. But haunted by an impulsive kiss Rochelle gave him fifteen years ago, her unexpected return has him rethinking things. He's been given a second chance to win her heart. And this time, he plans to succeed. Rochelle barely remembers Sandy, but she's drawn to his goodness. But just when she thinks she's found peace, her past catches up with her, and she finds herself in danger of losing the only safe haven she's ever known"--